Effects Of Ultraviolet Treatment On The Mechanical And Physical Properties Of Edible Starch Blend Films - Mat Salleh, Ummi Shafiqah (2011)
Edible films made from sago, mung bean and corn starches were prepared using glycerol as the plasticizer, and then they were treated under ultraviolet (UV) radiation for 1, 2 and 3 h exposure time. Different blends were made by varying the ratios of sago: mung bean and sago: corn starches as follows: 100:0, 75:25, 50:50, 25:75, and 0:100. The pasting properties and amylose content of the starches then were measured. Control (untreated) and ultraviolet (UV) treated films were evaluated for thickness, mechanical properties, water vapor permeability (WVP), water solubility,